CLINICAL AND ANAMNESTIC CHARACTERISTICS OF PATIENTS WITH GESTATIONAL DIABETES MELLITUS (Modern American Journal of Medical and Health Sciences, 2025)
Gestational diabetes mellitus (GDM) is a disease characterized by hyperglycemia, first detected during pregnancy, but does not meet the diagnostic criteria for manifest diabetes mellitus (DM). Hyperglycemia during pregnancy is a risk factor for complications from both the mother and the fetus, with about 80% of all cases of hyperglycemia being gestational diabetes mellitus (GDM). A number of risk factors are identified in patients with gestational diabetes mellitus, among which the most significant are family predisposition to diabetes mellitus, overweight, obstetric history, aggravated by preeclampsia and fetal macrosomia.